Analisis Learning Obstacles Siswa Kelas VIII Pada Materi Segitiga Rosalia Anisa - Rosalia Anisa; Sandie Sandie; Muchtadi Muchtadi (International Forum of Researchers and Lecturers, 2023)
This study aims to determine the learning obstacles associated with the triangle material and the factors that cause it. The participants in this study were class VIII students of SMPN 1 Sengah Temila and mathematics teachers. This study uses a qualitative method. Data collection techniques in this research used observation, measurement techniques (tests), interviews, and documentary studies. The data was analyzed qualitatively to determine students' learning obstacles in class VIII triangle material at SMPN 1 Sengah Temila. The results of this study are that students experience ontogenic barriers, namely obstacles related to one's mental readiness, epistemological, namely students' knowledge that has a limited context, and didactical obstacles related to teaching materials, or learning offerings used by the teacher. The obstacles experienced by students are learning obstacles to types of triangles, determining triangle images and triangle concepts.